Age-Related Influences of Prior Sleep on Brain Activation during Verbal Encoding - Jonelis, Michelle B.; Drummond, Sean P.; Salamat, Jennifer S.; McKenna, Benjamin S.; Ancoli-Israel, Sonia; Bondi, Mark W. (Frontiers in Neurology, 2012)
Disrupted sleep is more common in older adults (OA) than younger adults (YA), often co-morbid with other conditions. How these sleep disturbances affect cognitive performance is an area of active study. We examined whether brain activation during verbal encoding correlates with sleep quantity and quality the night before testing in a group of healthy OA and YA. Twenty-seven OA (ages 59-82) and twenty-seven YA (ages 19-36) underwent one night of standard polysomnography. Twelve hours post-awakening, subjects performed a verbal encoding task while undergoing functional MRI. Analyses examined the group (OA vs. YA) by prior sleep quantity (Total Sleep Time (TST)) or quality (Sleep Efficiency (SE)) interaction on cerebral activation, controlling for performance. Longer TST promoted higher levels of activation in the bilateral anterior parahippocampi in OA and lower activation levels in the left anterior parahippocampus in YA. Greater SE promoted higher activation levels in the left posterior parahippocampus and right inferior frontal gyrus in YA, but not in OA. The roles of these brain regions in verbal encoding suggest, in OA, longer sleep duration may facilitate functional compensation during cognitive challenges. By contrast, in YA, shorter sleep duration may necessitate functional compensation to maintain cognitive performance, similar to what is seen following acute sleep deprivation. Additionally, in YA, better sleep quality may improve semantic retrieval processes, thereby aiding encoding.